Ultralow Voltage, OTFT‐Based Sensor for Label‐Free DNA Detection. (2nd October 2012) - Lai, S.; Demelas, M.; Casula, G.; Cosseddu, P.; Barbaro, M.; Bonfiglio, A.
<x xml:space="preserve">Abstract</x> An organic ultralow voltage field effect transistor for DNA hybridization detection is presented. The transduction mechanism is based on a field‐effect modulation due to the electrical charge of the oligonucleotides, so label‐free detection can be performed. The device shows a sub‐nanometer detection limit and unprecedented selectivity with respect to single nucleotide polymorphism. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>